Geographical distance and news diffusion associating with the sentiment of tweets: Case Study on London Bridge Attack 2017 - Teh, Phoey Lee *; Low, Jin Quan; Si, Yain-Whar (2020)
This article aims to explore how could distance affect news diffusion and polarity of the sentiment. Understanding the estimation potential point of origin of news diffusion can allow time to control or monitor the potential of fake news to continue to disperse. In this case, we collect a total of 10,427 English tweets posted 1 hour after the real incident of London bridge attack. Taking into consideration that the ground zero as the place of attack, for an accumulating buffer of radius expanding with 400km from ground zero geographically, we organise tweets into ten clusters sets and analyse it. News diffusion level associating with the polarity of the sentiment of news discussed, and the type of terms that frequently used within the radius are also analysed.